Adaptive Playback Control: A Framework for Cinematic VR Creators to Embrace Viewer Interaction - Tong, Lingwei; Lindeman, Robert W.; Regenbrecht, Holger (Frontiers in Virtual Reality, 2022)
Content creators have been trying to produce engaging and enjoyable Cinematic Virtual Reality (CVR) experiences using immersive media such as 360-degree videos. However, a complete and flexible framework, like the filmmaking grammar toolbox for film directors, is missing for creators working on CVR, especially those working on CVR storytelling with viewer interactions. Researchers and creators widely acknowledge that a viewer-centered story design and a viewer's intention to interact are two intrinsic characteristics of CVR storytelling. In this paper, we stand on that common ground and propose Adaptive Playback Control (APC) as a set of guidelines to assist content creators in making design decisions about the story structure and viewer interaction implementation during production. Instead of looking at everything CVR covers, we set constraints to focus only at cultural heritage oriented content using a guided-tour style. We further choose two vital elements for interactive CVR: the narrative progression (director vs. viewer control) and visibility of viewer interaction (implicit vs. explicit) as the main topics at this stage. We conducted a user study to evaluate four variants by combining these two elements, and measured the levels of engagement, enjoyment, usability, and memory performance. One of our findings is that there were no differences in the objective results. Combining objective data with observations of the participants' behavior we provide guidelines as a starting point for the application of the APC framework. Creators need to choose if the viewer will have control over narrative progression and the visibility of interaction based on whether the purpose of a piece is to invoke emotional resonance or promote efficient transfer of knowledge. Also, creators need to consider the viewer's natural tendency to explore and provide extra incentives to invoke exploratory behaviors in viewers when adding interactive elements. We recommend more viewer control for projects aiming at viewer's participation and agency, but more director control for projects focusing on education and training. Explicit (vs. implicit) control will also yield higher levels of engagement and enjoyment if the viewer's uncertainty of interaction consequences can be relieved.